The Quantitative Consequences of Raising the U.S. Saving Rate - Lewis, Kenneth A.; Seidman, Laurence S. (The Review of Economics and Statistics, 1991)
The authors investigate the consequences of a permanent unphased increase in the U.S. gross saving rate. They find that "the sacrifice time"–the time that elapses until consumption surpasses the value it would have had under the initial saving rate–is roughly six years and is insensitive to the percentage increase in the saving rate ([Delta sub s]). The percentage gain in output at the end of decade–" the decade gain"–is roughly 26% of [Delta sub s], while the percentage gain in consumption is roughly 8% of [Delta sub s]. The "saving rate return"–the internal rate of return on a permanent increase in the saving rate–is roughly 16% and is insensitive to [Delta sub s]. Copyright 1991 by MIT Press.